Practicing Interdisciplinarity (De Gruyter, 2024)
A representation of the experiences and yields of the interdisciplinary work of a humanities and social science research training group with disciplinary breadth as well as historical depth. The disciplines range among others from ancient history through music didactics to sociology, and theology. Pairs of experienced and young scholars jointly reflect on their individual and collective experiences with joint interdisciplinary research.